2009
DOI: 10.1016/j.tsf.2009.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of silicidation of Ta filaments in HWCVD of thin film silicon

Abstract: a b s t r a c t a r t i c l e i n f oAvailable online xxxx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Radio-frequency alternating current instead of direct current has been used to heat the Ta catalyst wire, which decreases the Si content in the catalyst bulk and suppresses the formation of thick Si deposits on its surface because of the skin effect of the alternating current [11,18]. Annealing of the catalyst in H 2 ambient or in vacuum at a high temperature is beneficial to increase its lifetime [24,25], but that still cannot avoid the silicide growth during the reaction. Recently, Honda and co-workers have reported on surface carbonization of W wire for Cat-CVD of Si films [20,26].…”
Section: Introductionmentioning
confidence: 99%
“…Radio-frequency alternating current instead of direct current has been used to heat the Ta catalyst wire, which decreases the Si content in the catalyst bulk and suppresses the formation of thick Si deposits on its surface because of the skin effect of the alternating current [11,18]. Annealing of the catalyst in H 2 ambient or in vacuum at a high temperature is beneficial to increase its lifetime [24,25], but that still cannot avoid the silicide growth during the reaction. Recently, Honda and co-workers have reported on surface carbonization of W wire for Cat-CVD of Si films [20,26].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of deposition time dependent measurements it was shown that an increase in silicon content in the tungsten filament continuously increased with time, while the silicon content in the tantalum filament saturates rather quickly [10]. The emissivity of Ta is expected to be lower than its silicide Ta 5 Si 3 [11] and hydrogen atom production or silane dissociation by tantalum is twice as efficient compared to tungsten at the same deposition condition [12]. From the analysis of FTIR spectra of a-Si:H films deposited at different T s (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, several solutions have been proposed to minimize the degradation of the filaments [4][5][6][7][8][9][10][11]. Although some progress has been achieved especially in increasing the structural life time [4][5][6][8][9][10], i. e. the time for which the filament does not break, no definitive solution has been found so far, neither in stabilizing the filaments without affecting their catalytic activity [7], nor in a filament regenerating procedure which is not time consuming [11]. Furthermore, as we show in a parallel publication, the catalytic properties of the filaments are compromised since the catalytic surface starts to be affected by degradation [12].…”
Section: Introductionmentioning
confidence: 99%